2022
DOI: 10.3389/fnut.2022.1032810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aflatoxin B1 exposure on the progression of depressive-like behavior in rats

Abstract: While it is well documented that aflatoxin B1 (AFB1); one of the most toxic food contaminants is linked to the development of depression. However, the mechanism on how it affects the gut and brain health leading to depressive-like behavior remains unclear. This study was conducted to determine the effect of AFB1 on the progression of depressive-like behavior. Thirty-two (n = 32) male Sprague Dawley rats were randomly allocated into four groups: control, low-dose (5 μg AFB1/kg), high-dose (25 μg AFB1/kg) and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…The fact that AFB1 slowed the growth of the rats may be mostly due to these reports. Depression of appetite may be to blame for the drop in body weight [ 38 ]. Aflatoxins were also noted to reduce the formation of volatile fatty acids (VFA), proteolysis, and gastrointestinal tract motility [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that AFB1 slowed the growth of the rats may be mostly due to these reports. Depression of appetite may be to blame for the drop in body weight [ 38 ]. Aflatoxins were also noted to reduce the formation of volatile fatty acids (VFA), proteolysis, and gastrointestinal tract motility [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased adrenal weight in stressed animals suggests the hyperactivation of the HPA axis [ 52 ]. In CUMS animals, the adrenal gland weight increases [ 56 ]. Similar to previous studies, our results showed that the adrenal gland weight of the CUMS/saline group was higher than that of the non-CUMS group.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure (15-75 ng/mL to 6-h post fertilization embryo and 7 days post fertilization larvae) to AFB 1 has also been found associated with the motor dysfunction in zebra fish embryos leading to developmental defects and musculoskeletal issues (He et al, 2023;Wu et al, 2019). Subramaniam et al (2022) studied the effect of 4 weeks of chronic exposure of a low dose of 5 mg/kg and a high dose of 25 mg/kg of AFB 1 on the progression of depressive-like behavior in rats. They hypothesized AFB 1 can induce this type of behavior through disruption of the Hypothalamus-Pituitary-Adrenocortical axis due to generation of oxidative stress in the brain.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Subramaniam et al. (2022) studied the effect of 4 weeks of chronic exposure of a low dose of 5 mg/kg and a high dose of 25 mg/kg of AFB 1 on the progression of depressive‐like behavior in rats. They hypothesized AFB 1 can induce this type of behavior through disruption of the Hypothalamus–Pituitary–Adrenocortical axis due to generation of oxidative stress in the brain.…”
Section: Aflatoxin Toxicity and Health Impactmentioning
confidence: 99%